STEM ESD-Based Learning with "Arduino Uno-Based Trash Can" to Improve Students' Critical Thinking Skills and Sustainable Awareness in Learning Environmental Pollution - Annisa, Dea Puspha; Kaniawati, Ida; Eliyawati, Eliyawati (Jurnal Penelitian dan Pembelajaran IPA, 2024)
STEM ESD-based learning with "Arduino UNO-Based Trash Can" is a learning model that integrates STEM learning with the principles of Education for Sustainable Development (ESD). ESD recognizes critical thinking and sustainable awareness as the competencies that help develop one's personal qualities for tackling sustainability challenges in the future. Therefore, this research investigated whether STEM ESD-based learning with "Arduino UNO-based Trash Can" improves students' critical thinking skills and sustainable awareness in learning about environmental pollution. A pre-experimental design with one group pretest-posttest design was employed. The participants in this research study were thirty-six 7th-grade junior high school students in one public school in Subang. Critical thinking skills were assessed through ten essay questions and evaluated using a rubric on a scale of zero to three. Sustainable awareness was measured by a 4-point Likert scale questionnaire comprising 27 statements. Data from both instruments were analyzed using IBM SPSS Statistics software. The results showed that the STEM ESD-based learning with "Arduino UNO-Based Trash Can" contributed positively to improving students' critical thinking skills. However, the improvement was not uniformly distributed among all indicators and remained low, with 0.202 of the N-Gain score. On the other hand, the study revealed that the STEM ESD-based learning with "Arduino UNO-Based Trash Can" did not significantly improve students' sustainable awareness, with only a 0.040 N-Gain score. This study's results contribute to future research or teaching as references for integrating STEM learning with ESD in presenting environmental pollution in the context of sustainability.